EAU-ESMO Consensus Statements on the Management of Advanced and Variant Bladder Cancer-An International Collaborative Multistakeholder Effort Under the Auspices of the EAU-ESMO Guidelines Committees - Witjes, J. Alfred; Babjuk, Marek; Bellmunt, Joaquim; Bruins, H. Maxim; De Reijke, Theo M.; De Santis, Maria; Gillessen, Silke; James, Nicholas; Maclennan, Steven; Palou, Juan; Powles, Tom; Ribal, Maria J.; et al. (European Urology, 2020)
Background: Although guidelines exist for advanced and variant bladder cancer management, evidence is limited/conflicting in some areas and the optimal approach remains controversial.
CRIS-Team WoS Importer:2020-01-28